Boundary-value problems for parametric ordinary differential equations - Karandzhulov, L. I. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
By using semiinverse matrices and a generalized Green's matrix, we construct solutions of boundary-value problems for linear and weakly perturbed nonlinear systems of ordinary differential equations with a parameter in boundary conditions.